2014
DOI: 10.1007/s00276-014-1279-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of mandibular foramen in macerated skulls to contribute to the development of sagittal split ramus osteotomy (SSRO) technique

Abstract: The values found in this study, considering gender, age and ethnic group, can be used as a parameter to carry out the sagittal split ramus osteotomy technique, making it more predictable and with less risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
8
3
Order By: Relevance
“…This means that the distance from mandibular foramen to mandibular notch (MF-MN) was close in males to females. In contrast to a study conducted on a Chilean population showed that the distance from the mandibular foramen to the mandibular notch (MF-MN) in males (24.35mm) was greater than in females (22.0mm) (21) .…”
Section: Discussioncontrasting
confidence: 78%
“…This means that the distance from mandibular foramen to mandibular notch (MF-MN) was close in males to females. In contrast to a study conducted on a Chilean population showed that the distance from the mandibular foramen to the mandibular notch (MF-MN) in males (24.35mm) was greater than in females (22.0mm) (21) .…”
Section: Discussioncontrasting
confidence: 78%
“…We have not found the assimilated shape for black individuals, and for white individuals this shape was found in only 3.1 %. The literature reports important racial differences in studies with mandibles (Alves & Deana, 2014), however we did not find any other study correlating race and shape of lingula.…”
Section: Discussioncontrasting
confidence: 80%
“…Based on our results, we emphasize that in planning a surgery involving the region of lingula, such as sagittal split ramus osteotomy (SSRO) technique, the surgeon must take into account aspects such as gender, race, and shape of lingula. Another important issue that should be considered is a possible anatomical variation in the medial region of the ramus of mandible, where there may be an accessory mandibular foramen located above the lingula [ 21 , 22 ] or near the mandibular notch [ 23 ]. Such variations are not common but result in increased risk of complications involving the inferior alveolar nerve [ 21 ].…”
Section: Discussionmentioning
confidence: 99%